2019
DOI: 10.17979/sportis.2020.6.1.5730
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de una Unidad Didáctica de educación postural en 1º de la Educación Secundaria Obligatoria

Abstract: El objetivo de este estudio fue conocer la prevalencia de dolor lumbar y evaluar los efectos de una unidad didáctica de educación postural sobre los conocimientos teóricos de la salud de la espalda, así como los efectos de la misma sobre la resistencia de la musculatura extensora, inclinadora y flexora del tronco en alumnado de 1º de ESO. Participaron 18 discentes (10 chicos y 8 chicas) de 12.22 ± .43 años de edad de un colegio perteneciente a la Comunidad Valenciana. Se realizó una evaluación inicial (Pretest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Despite this, other authors have also shown the effectiveness of non-gamified interventions. In this sense, Allen, Hannon, Burns and Williams (2014) and Cabrera-González, Serrano-Durá, Fargueta and Monleón (2020) found that an intervention aimed at improving the musculature of the trunk and core of the students in PE classes produced significant improvements in the resistance of said musculature.…”
Section: Discussionmentioning
confidence: 98%
“…Despite this, other authors have also shown the effectiveness of non-gamified interventions. In this sense, Allen, Hannon, Burns and Williams (2014) and Cabrera-González, Serrano-Durá, Fargueta and Monleón (2020) found that an intervention aimed at improving the musculature of the trunk and core of the students in PE classes produced significant improvements in the resistance of said musculature.…”
Section: Discussionmentioning
confidence: 98%